Understanding Resilience: Coping with Occupational Stress in Healthcare Professions (International Journal of Physiotherapy, 2024)
Background: The demanding nature of their employment sometimes causes severe occupational stress among health care practitioners. Burnout, compassion fatigue, and a decline in job satisfaction can result from these pressures. However, emotional resilience, the capacity to adjust to and prosper in difficult circumstances, can be a vital defense against these unfavorable consequences.Methods: This review focused mainly on healthcare professionals, including doctors, dentists, nurses, social workers, psychologists, and counselors. This review examined resilience variables, coping strategies, and occupational stress. The primary goal of this review was to identify the main sources of occupational stress that are common in each field. Understanding these pressures is essential because it sheds light on the difficulties encountered by medical practitioners. The second goal was to analyze the varied coping strategies these professions use to handle stress. These systems are essential because they support clinicians in keeping their mental health in check and providing high-quality treatment to their patients. The third goal was to assess how organizational and individual variables affect building resilience.Results: This evaluation thoroughly examined the coping strategies and resilience elements essential for effectively managing the complex challenges associated with their positions. In all areas of healthcare, approaches such as actively pursuing interpersonal support, promoting holistic well-being, and cultivating supportive work environments are recognized as essential elements for efficiently navigating the field's challenges.Conclusion: Resilience is not only a personal quality; environments and organizations may also impact it. Finally, this study aimed to identify the present research gaps and recommend future research areas.